(3GdHhds - (3ESMGb Hf SdjeGf GdGSQGFjdj, CHh jYbhH,J (B320 (3g` s
(3ChdgG (B:s
(3cJGH eLehY ef CbGhjd GdChGFd aj eYQaI GdHhd hCbSGeg hOdGFdg eeG Yfj HLeYg hJCdjag hQJHg Ydi YTQI CHhGH s
(3BNQgG (B:s
(3BNQg eHJhQ, jfJgj NdGd GdHGH GdSGOS aj bhGe GdHhd, hBNQ GdehLhO(B: (3hefg eG HGd ZdjXkG Ke HUYhHI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B244 - (3U(B260s
(3QJHg Ydi YTQI CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
GAL - (3GdLRA (B1 - (3U (B235 ; GAL - (3GdLRA (B1 - (3U (B236 ; GALS - (3GdLRA (B1 - (3U (B421 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B40 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs